Analisa Desain High Availability dan Uji Reabilitas Cloud Storage - Prabowo, Hari Yudho; Mukti, Aan Restu; Suryayusra; Ariyadi, Tamsir (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The growth of the Internet has brought about significant changes in how we store data. Common data storage media include hard disks, flash drives, and CDs. With the advancement of technology, cloud storage has emerged as a new alternative in the world of storage. In this regard, two leading cloud storage platforms, Owncloud and Nextcloud, have evolved into popular options. The purpose of this research is to evaluate the level of High Availability and reliability of Owncloud and Nextcloud cloud storage platforms. This is accomplished by conducting load testing and simulating failure scenarios to assess the platforms' ability to ensure data access during disruptions and enhance performance under high loads. The research methodology used is the Network Development LifeCycle (NDLC). The software employed as the operating system is Ubuntu Server 20.04, and for web server load testing, Netdata and Nagios are used to monitor the system. The results of this research provide comprehensive information on the high availability and reliability of Owncloud and Nextcloud cloud storage platforms in modern computing environments.